Corn Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C. (My University, 2000)
This publication provides estimated cost and returns for forward farm planning for corn in south central Kansas.
MF2157_2000_10
Keywords: MF2157; Crops; Economics; MF